Prevalência de genes relacionados com a patogenicidade e produção de enzimas extracelulares em Aeromonas sp. - Fadanelli, Raquel (My University, 2018)
Aeromonas are considered as emerging animal and human pathogens causing diarrhea and extraintestinal infections, such as wound infection and septicemia. Several extracelular enzymes and toxins have been pointed as potential virulence factors in Aeromonas. However, the importance of each particular fator or their interation during the pathogenic processes is not well defined. In the presente work, the distribution and phenotypic activity of the genes encoding the aerolysin/hemolysin, serine protease, metalloprotease, lipase and glycerophospholipid-cholesterol acyltransferase (GCAT) were investigated in 15 type strains, representing 12 of the 14 species of the genus, and 30 clinical and environmental isolates of Aeromonas. The former genes were found to be highly conservered among the genus and isolates. The lipA gene was identified in 93% of the samples and may be used as a target gene for the rapid identidication of Aeromonas in clinical, food and environmental samples. Aerolysin, elastase, lipase and GCAT genes were presente in both clinical and environmental isolates. Conversely, ahpA gene was more prevalente in clinical isolates, indicating their direct or indirect role in the mechanism of pathogenesis of thease microorganisms. Variation on the extracelular enzymes eas evidenced among the species and isolates of Aeromonas. However no relation was found between enzymatic activities and clinical isolates. The relation between hemolytic activity on human blood and the presence of aerolysin/hemolysin gene (aerA) can be seen as na indicative that aerolysin are particularly active against human erythrocytes.
As bactérias do gênero Aeromonassão consideradas como patógenos emergentes de animas e humanos, causando diarreia e infecções extra intestinais tais como, infecções de pele e septicemia. Várias enzimas extracelulares e toxinas tem sido apontadas como potenciais fatores de virulência em Aeromonas. Contudo, a importância de cada fator em particular ou sua interação durante os processos patogênicos não está bem definida. No presente trabalho, a distribuição e a atividade fenotípica dos genes que codificam aerolisina/hemolisina, serina protease, metaloprotease, lipase e glicerofosfolipideo-colesterol aciltransferase (GCAT) foram investigados em 15 linhagens tipos, representando 12 das 14 espécies do gênero, e 30 isolados clínicos e ambientais em Aeromonas. Os genes analisados estão altamente conservados entre os gêneros e os isolados. O gene lipA foi identificado em 93% das amostras, podendo ser usado como um gene alvo para a rápida identificação de Aeromonas em amostras clínicas, ambientais e de alimentos. Os genes que codificam aerolisina, elastase, lipase e GCAT estiveram presentes tanto nos isolados clínicos como nos ambientais. Contrariamente, o gene ahpA foi mais prevalente nos isolados clínicos, indicando papel direto ou indireto no mecanismo patogênese destes microrganismos. Variações em relação às enzimas extracelulares foram evidenciadas entre as espécies e os isolados de Aeromonas. Contudo, nenhuma relação foi encontrada entre as atividades enzimáticas e os isolados clínicos. A relação entre atividade hemolítica sobre o sangue humano e a presença do gene aerolisina/hemolisina (aerA) pode ser considerada um indicativo de que aerolisina seja particularmente ativa contra eritrócitos humanos.
Keywords: Bactérias gram-negativas; Aeromonas; Enzimas extracelulares; Gram-negative bacteria; Aeromonas; Extracellular enzymes